Structural analysis and anticoagulant activities of three highly regular fucan sulfates as novel intrinsic factor Xase inhibitors. (1st September 2018) - Shang, Feineng; Mou, Rongrong; Zhang, Zhidong; Gao, Na; Lin, Lisha; Li, Zhongkun; Wu, Mingyi; Zhao, Jinhua
Graphical abstract: Highlights: Three fucan sulfates with distinctive simplest repeating units were described. Their sequences reveal the structural diversity in the sea cucumber species. They exhibit strong inhibition of the intrinsic coagulation pathway. The ability of fucan sulfate to inhibit intrinsic factor Xase was reported. Abstract: Fucoidan or fucan sulfate, a sulfated polysaccharide from algae or echinoderm mainly containing fucoses, possesses complex chemical structure and various biological activities. Herein, three fucan sulfates consisted of distinctive simplest repeating units were isolated from Holothuria fuscopunctata, Thelenota ananas and Stichopus horrens . The structural sequences of these fucan sulfates from H. fuscopunctata, T. ananas and S. horrens are →4-α-l -Fuc p -(3 S O3 − )-1→, →4-α-l -Fuc p -(2 S O3 − )-1→ and →3-α-l -Fuc p -(2 S O3 − )-1→, respectively, revealing the existence of the highly regular homogeneous fucan sulfates and their structural diversity in the sea cucumber species for the first time. Pharmacological assays indicated their specific sulfation pattern and position of the glycosidic linkage may contribute to the anticoagulant action. Further mechanism analysis suggested that these fucan sulfates may exhibit strong inhibition of the intrinsic coagulation pathway by targeting the intrinsic coagulation factor Xase. Our results provide novel information to enrich knowledge on structural types of fucan sulfate and to illustrate its functionality.